POLSKA POLITYKA GOSPODARCZA A INTERNACJONALIZACJA I GLOBALIZACJA - Gorynia, Marian (Wydział Prawa i Administracji UAM, 2006)
Certain recommendations, or propositions for the directions of Polish economic policy are presented. Three key conditions upon which the place of Poland’s economy in the international environment depends have been analysed as those which will ultimately determine the advantages of the international division of labour resulting in a possible enrichment and prosperity. Those conditions are: a) completion of the transformation process, whose significance will be diminishing in time; b) Poland’s EU membership - and especially Poland’s economic relations with other member states; and c) globalisation, which will ultimately be decisive for Poland’s role in the world’s economy, but which, alongside many opportunities, brings many threats for the Polish economy as well. The first group of recommendations (propositions) presented in the paper point to the importance of building a long term strategy for Polish economy in the competitive market, and the other proposes forms and directions of supporting the competitiveness of Polish businesses and products in the Single European Market.
POLISH ECONOMIC POLICY VS INTERNALISATION AND GLOBALISATION